Evaluation of the material’s damage in gas turbine rotors by instrumented spherical indentation (Fracture and Structural Integrity, 2014)
Experimental indentations are carried out on items of two different materials, taken in severallocation of various components from high pressure gas turbine rotor which have seen an extensive service. Thecomponents object of investigation consisted in 1st and 2nd high pressure turbine wheels made in nickel-basesuperalloy (Inconel 718), the spacer ring (Inconel 718) and the compressor shaft made in CrMoV low alloy steel(ASTM A471 type10).Aim of the work is to set up the capability of the instrumented spherical indentation testing system to evaluatevariations in the material properties due to damage, resulting from temperature field and stresses acting oncomponents during service. To perform this task load-indentation depth curves will be acquired in variouszones of the above mentioned components. The analysis of the results has allowed to identify an energyparameter which shows a linear evolution with the mean temperature acting on the components.
Keywords: Instrumented indentation